Image fusion, based on data from sources of a various spectral range - D. S. Sharak; E. I. Mikhnionok; A. S. Shein; A. V. Khizhniak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The complex approach of earth surface and airspace data processing with use of images from sources of a various spectral range is considered in the article. Methods and algorithms of image fusion according to several video information sources are presented. The analysis of existing image fusion devices are carried out, and the function chart of experimental module realizing known fusion video sequences algorithms is presented.